Interpersonal contact among the faculty members of College of Arts and Social Sciences factors, effects, and adjustments - de Claro, Loressa Joy S. (Langkit : the Official journal of the College of Arts & Social Sciences Mindanao State University-Iligan Institute of Technology, 2012)
This study aims to find out the factors of interpersonal contact, their effects and the adjustment employed of the young, middle and late adult faculty members of the College of Arts and Social Sciences. The data show that both groups often experience personal and social factors of interpersonal contact, while middle-to late adult faculty members rarely experience career factors. This means that young adults often engage in interaction while the middle- to late adults rarely engage in interaction. Moreover, both groups often experience personal and career effects of interpersonal contact but rarely experience social effects. On the other hand, middle- to late adult faculty members often experience negative stereotyping and group-serving bias in their interpersonal contact. Emotional and cognitive forms of adjustments are often employed by both age groups. Lastly, there is no significant difference between the two age groups in terms of factors experienced, effects and adjustments employed. It is recommended that the Human Resource Department of MSU-Iligan Institute of Technology will conduct seminar-workshops and team- building trainings that will further enhance the faculty members' interpersonal contact.